Estrutura trófica da comunidade de peixes de igarapé de várzea estuarina - Baía de Marajó - Pa - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1996)
Marajó Bay belongs to the Amazonian estuary, located south of Marajó Island, and receives the discharge of the Amazon and Tocantins rivers. The variation in salinity is the main factor that interferes with the composition and distribution of species. The ichthyofauna in the estuary changes in the different periods (i) flood; (ii) transition and (iii) summer, presenting freshwater, marine and estuarine species. The aim of this work is to demonstrate the trophic relationships between resident and invasive species in the estuary and to infer about the role of the estuarine floodplain streams in the life cycle of these species. The specimens were collected by hand-hooked puçá de arrasto from three different points in Marajó Bay (i) Igarapé Tucunduba (Belém-PA), (ii) Igarapé Paracuri (lcoaraci), (iii) Vigia (PA), in three environments: igarapé, beach and bay. Their stomachs were extracted and analyzed in the laboratory. The food items were classified into 36 categories and their quantity was estimated considering subjectively the degree of repelling, from values of: (I) from 0 to 25%, (2) from 26 to 50%, (3) from 51 to 75% and (4) from 76 to 100%. The individuals had a mean standard length of 4.51 in, most of them being juveniles. Regarding the nature of the food, the items of indigenous origin. The main item found in the stomachs of most species was from the Crustacea Class, Palaemonidae and Portunidae families and several other microcrustaceans in the young and adult form. The native food items contributed with more than 72% of the diet composition of the studied species, differing from the diet composition of the Central Amazon fish communities, where allochthonous items are predominant. The other food items found were: fish, detritus, adult insects, insect larvae, Cirripedia, Polychaeta, phytoplankton, and Mollusca.
Trophic structure of a fish community from an estuarine floodplain stream - Marajó Bay - Pa
Keywords: Estuarina; Baía de Marajó; Dulciaquícolas; Marinhas; Crustacea; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA